A densely modified M2+-independent DNAzyme that cleaves RNA efficiently with multiple catalytic turnover. Issue 7 (16th January 2018) - Wang, Yajun; Liu, Erkai; Lam, Curtis H.; Perrin, David M.
Abstract : Modified dNTPs permit selection of DNAzymes that cleave RNA targets in the absence of a divalent metal cation (M 2+ ) to meet a long-standing goal in bioorganic chemistry. Abstract : Sequence-specific cleavage of RNA targets in the absence of a divalent metal cation (M 2+ ) has been a long-standing goal in bioorganic chemistry. Herein, we report the in vitro selection of novel RNA cleaving DNAzymes that are selected using 8-histaminyl-deoxyadenosine (dA im TP), 5-guanidinoallyl-deoxyuridine (dU ga TP), and 5-aminoallyl-deoxycytidine (dC aa TP) along with dGTP. These modified dNTPs provide key functionalities reminiscent of the active sites of ribonucleases, notably RNase A. Of several such M 2+ -free DNAymes, DNAzyme 7-38-32 cleaves a 19 nt all-RNA substrate with multiple-turnover, under simulated physiological conditions wherein only 0.5 mM Mg 2+ was present, attaining values of k cat of 1.06 min −1 and a K M of 1.37 μM corresponding to a catalytic efficiency of ∼10 6 M −1 min −1 . Therefore, Dz7-38-32 represents a promising candidate towards the development of therapeutically efficient DNAzymes.